Influence of Dietary Formulation Methods on Response to Arginine and Lysine in Diets for Young Broiler Chickens - Waldroup, P.W.; Oviedo-Rondon, E.O.; Fritts, C.A. (International Journal of Poultry Science, 2006)
A study was conducted to compare response of young broiler chicks to various levels of Lys and Arg using two different dietary approaches. In both diet types, a 4 x 5 factorial arrangement with Lys levels of 1.1, 1.2, 1.3, and 1.4% and Arg levels of 1.25, 1.35, 1.45, 1.55, and 1.65% was used. All other essential amino acids were at least 110% of NRC (1994). Corn, soybean meal, and corn gluten meal (CGM) of known composition were used. In the first diet set (BASAL + AA) a diet that contained 1.1% Lys and 1.25% Arg was fortified with L-Lysine HCl and L-Arg to provide the various levels of Lys and Arg. In the second dietary set (INTACT) each of the 20 diet combinations was formulated independently using intact protein sources to provide the desired Lys and Arg levels with the primary difference being in amount of CGM that varied from 0 to 33%. Data were subjected to ANOVA as factorial arrangement of treatments. Conflicting results between the two diet types existed. In BASAL+AA diets there were no significant differences in BW or FCR due to Lys; 1.35 to 1.45% Arg was necessary for optimum FCR. Although the Lys x Arg interaction was not significant the reduction in BW or FCR at high Lys with low Arg interaction was not significant, the reduction in BW or FCR at high Lys with low Arg appeared primarily responsible for the increased Arg needs. In the INTACT series there were significant interactions in BW and FCR for Arg and Lys, but these appeared to be associated with reduced performance on diets high (15-30%) in CGM. In a parallel study these levels of CGM reduced performance due to reduced feed intake. Thus, differences in diet type may influence response to Arg and Lys due to factors other than amino acid level per se.